Production and perception of speech in children with cochlear implants - Mildner, Vesna (2011)
The aim of the study was to analyze the production and perception of speech in severely hearing-impaired children (pre-school and elementary school level) using cochlear implants. It focused on the five Croatian vowels (/i, e, a, o, u/), fricatives /s/ and /š/ and affricates /c/ and /č/. The vowels were analyzed in terms of the vowel space defined by the first and second formant frequencies. The perception of fricatives and affricates was analyzed in terms of voicing, place of articulation and manner of articulation. The production of fricatives was analyzed in terms of their noise frequencies, and the production of affricates was analyzed with respect to duration and fricative-stop timing. Perception was tested by means of an auditory forced-choice minimal pairs test and production was tested by having the subjects name everyday objects presented in pictures and numbers 1 through 10. The perception data reveal that there are more confusions between vowels that are close to each other (e.g. a-e, or o-u) than between the more distant ones (e.g. i-a). With respect to consonants, manner of articulation was the easiest, with voicing and place of articulation only slightly above chance level. The vowel production results reveal formant-defined vowel space that is smaller in area and fronted compared to hearing children’s data. Both fricatives had higher noise frequency than controls, with considerable overlap. The percentage of correctly produced affricates was low, with targets being most frequently substituted by fricatives. Overall duration was longer than in hearing children.
Projekt MZOS
ENG